BASIS OF SEXUAL DIFFERENTIATION AND ETHICAL ASPECTS OF INTERSEX - Vargas Barrantes, Élida (2013)
The new concept ofsexual diversity recognizes in sexuality a social and psychobiological construction, which goes far beyond genitality. Sexual diversity includes various intersex states, which are located as part of a continuum that goes beyond the traditional scheme that places us between two exclusive extremes of being a man or woman. The adjustment of intersex bodies involves not only the diagnosis but also hormonal and surgical interventions, whose sole purpose is to control bodies that carried away by their very nature, lead pose a threat to a binary scheme of both sexes / genders. However, it should be the individual with intersex syndrome who decides about what is best for their overall development and according to their sexual preferences. As part of the diversity of human nature itself, the individual is in every right and duty to decide for their own future!